Penilaian Pada Kualitas Laporan Keuangan melalui Analisis Rasio Profitabilitas di Sekolah Menengah Pertama Kabupaten Sleman - Melvin Rahma Sayuga Subroto Subroto (Journal of Trends Economics and Accounting Research, 2023)
This study aims to analyze the assessment of the quality of school financial reports through profitability ratios, at XYZ Junior High School in Sleman Regency. In this study the profitability ratio is calculated by net profit margin. Another objective of this study is to determine the level of profit at XYZ Junior High School in Sleman Regency. This research uses a qualitative approach with descriptive analysis methods. The sample used is financial reporting. The sample was determined using net profit margin and then using purposive sampling with respondents as operational director, finance department. Data collection techniques were carried out by means of observation, interviews and documentation. As for the data analysis technique is done by data reduction, data presentation. The validity of the research data will be tested using data triangulation. The results of this study indicate that: 1) The liquidity ratio of XYZ Junior High School in Sleman Regency from the calculation of the net profit margin is said to be healthy. Judging from the calculation, it shows more than 20%, so that junior high school is said to be profitable. 2) The quality of the Junior High School's financial reports is appropriate, understandable.